Neurological recovery and antioxidant effect of erythropoietin for spinal cord injury: A systematic review and meta-analysis - Zhang, Ya-yun; Yao, Min; Zhu, Ke; Xue, Rui-rui; Xu, Jin-hai; Cui, Xue-jun; Mo, Wen (Frontiers in Neurology, 2022)
Background. To critically evaluate the neurological recovery effects and antioxidant effects of erythropoietin (EPO) in rat models of spinal cord injury (SCI). Methods. The PubMed, EMBASE, MEDLINE, ScienceDirect, and Web of Science were searched for animal experiments applying EPO to treat SCI to January 2022. Neurological function was assessed by the Basso, Beattie, and Bresnahan (BBB) scale, as well as cavity area and spared area. Molecular-biological analysis of antioxidative effects was determined by malondialdehyde (MDA) levels in spinal cord tissues. Meta-analysis were performed with Review Manager 5.4 software. Results. A total of 33 studies were included in this review. The results of the meta-analysis showed that SCI rats receiving EPO therapy showed a significant locomotor function recovery after 14 days compared with control, then the superiority of EPO therapy maintained to 28 days from BBB scale. Compared with the control group, the cavity area was reduced (WMD = -16.65, 95% CI [-30.74 to -2.55], P = 0.02) and spared area was increased (WMD =11.53, 95% CI [1.34 to 21.72], P = 0.03) by EPO. Meanwhile, MDA levels (WMD = -0.63 [-1.09 to -0.18], P = 0.007) were improved in the EPO treatment group compared with control, which indicated its antioxidant effect. The subgroup analysis recommended 5000 UI/kg is the most effective dose (WMD = 4.05 [2.23, 5.88], P＜0.0001), although its effect was not statistically different from that of 1000 UI/kg. Meanwhile, the different species, and models of animals, as well as administration of EPO did not affect the neuroprotective effect of EPO for SCI. Conclusions. This systematic review indicated that the neuroprotective effect of EPO was closely related to oxidative stress, and might be related to anti-apoptosis and increased autophagy. The mechanism exploration of EPO needs to be verified by experiments, and then carefully designed randomized controlled trials are needed to explore its neural recovery effects.